CAMPUS: an innovative web-based approach for simulative, flexible, case-oriented education in medicine - Riedel, Jens; Singer, Reiner; Leven, Franz-Josef; Geiss, Heiko; Tönshoff, Burkhard (Proceedings of ED-MEDIA 2000, 2000)
In medical education, Problem-Based Learning (PBL) is becoming appreciated more and more. The design and implementation of a problem-oriented medical curriculum, however, is very time-consuming for the educational staff. Case-based, Web-based training systems can help the educators to develop, implement, organise and reuse well-structured multimedia cases. For students, such a system can be used to improve and test their problem-solving competence. With respect to heterogeneous learning environments, the system should be flexible and adaptable.